Lógica 5 - Cuantificadores - Solís-Palma, Angie (My University, 2022)
Se presenta la definición de proposición abierta y los cuantificadores existencial y universal.

The definition of open proposition and the existential and universal quantifiers are presented.
Keywords: Proposición; Cuantificador; Matemáticas discretas; Proposition; Quantifier; Discrete mathematics